The Phenomenon of Sentiments and Love in Non-human Animals from the Ontological Point of View of Mulla Sadra. - Hamidreza, Mirzaei (Sophia, 2022)
In the whole universe, from the lowest beings to the highest ones, love permeates through the entire world of existence. Love is one of the hallmarks and perfections of existence in animals. This survey was done to illuminate and explain Mullah Sadra's ontological viewpoint on the entity of sentiments and the inborn and innate love in the existence of non-human animals. The analytic and descriptive method (library documentary) was used to conduct this study and research. An animal is one of the creatures in the essence of the existence that possesses its own perfect attributes. Animals have souls, the effects of which are life, perception, free choice, and emotions (love). Animals have an order for their existence, and they are attributed with perfection to the extent of their intensity and weakness. That is to say, all animals are not at the same level. Their perfection is also the same as their existence is. There is life, perception, and love in animals, but it depends on their proportion of existence. All animals are in love, but every animal having the highest share of its rank enjoys more love. Mullah Sadra's ontological principles in proving the existence and flow of love in animals are that the existence is 'original,' 'non-composite,' 'equivocal,' and 'coextensive' with life, conception and love, and 'God, the Almighty, is the true Beloved of all beings including animals' souls.' Evolutionarily, animals can only move to the point where humanity of human beings begins.